CORPORATE GOVERNANCE TERHADAP CUMULATIVE ABNORMAL RETURN - Destin Alfianika Maharani; Anastasia Anggarkusuma Arofah; Kartika Chandra Sari (J-LEE - Journal of Law, English, and Economics, 2022)
This study aims to determine the effect of corporate governance on cumulative abnormal returns in companies listed in the Corporate Governance Perception Index. The sample selection in this study used purposive sampling with the criteria of 1) Companies listed on the Corporate Governance Perception Index (CPGI) during the period 2017 - 2019, 2) Companies listed on the Corporate Governance Perception Index (CPGI) and listed on the Indonesia Stock Exchange (IDX). ) during the period 2017 – 2019, 3) Companies that publish annual reports during the period 2017 – 2019, 4) Companies that provide complete information on data regarding the required variables. Thus obtaining a sample of 36. The results in this study are the results show that corporate governance has a positive but not significant effect on cumulative abnormal returns.